Modern Marketing Education: Mode Ling Approach & E-Learning - Juslin, Heikki; Paldanius, Pasi (Ekonomika, 2002)
In marketing pedagogy the most important thing is to understand how the student creates competence and how the teacher can support the competence creation process. The competencies of a high level marketing specialist are connected with marketing planning and development. The main planning and development tools are models and information. The marketing students should learn how to work on a conceptual level using models and information but on the other hand he or she should learn thoroughly what marketing is all about in practice. This article describes how to combine scientific method and practical marketing reality. The combination of modeling approach and illustrative E-learning is called Model-based Action Learning Method.